Impact of the Good Behavior Game on special education teachers. Issue 4 (19th May 2018) - Hopman, Juliette A. B.; van Lier, Pol A. C.; van der Ende, Jan; Struiksma, Chris; Wubbels, Theo; Verhulst, Frank C.; Maras, Athanasios; Breeman, Linda D.; Tick, Nouchka T.
Abstract: This study tested effects of a program that offers teachers universal classroom management strategies, on teachers' burnout symptoms and self-efficacy, and their teaching behaviors. Data were collected from 147 teachers (mean age = 38.4 years, SD = 10.8) in 15 special secondary education schools for students with emotional and behavioral problems, at the start and end of the school year. Schools were randomly assigned to the experimental condition or a care-as-usual condition. Results show that the program impacted beneficially on self-reported levels of emotional exhaustion, and self-efficacy in engaging students and in classroom management, but not on teaching behaviors. Implications of this study for the professional development of teachers in special education and research are discussed.